Generic Decoding in the Sum-Rank Metric - Puchinger, Sven; Renner, Julian; Rosenkilde, Johan (Proceedings / IEEE International Symposium on Information Theory, 2020)
We propose the first non-trivial generic decoding algorithm for codes in the sum-rank metric. The new method combines ideas of well-known generic decoders in the Hamming and rank metric. For the same code parameters and number of errors, the new generic decoder has a larger expected complexity than the known generic decoders for the Hamming metric and smaller than the known rank-metric decoders.